The crystal structure of 3-(4-chlorophenyl)-1,5-di-p-tolylpentane-1,5-dione, C25H23ClO2 - Zheng Jun; Liu Sen; Zhang Yaru; Huang Xianqiang (Zeitschrift für Kristallographie - New Crystal Structures)
C25H23ClO2, orthorhombic, P212121, a = 5.5648(5) Å, b = 17.6062(15) Å, c = 21.5033(19) Å, V = 2106.8(3) Å3, Z = 4, R gt(F) = 0.0529, wR ref(F 2) = 0.1371, T = 298 K.